Fat oxidation defect presenting with overwhelming ketonuria. Issue 5 (1st November 2002) - Wraige, E; Champion, M P; Turner, C; Dalton, R N
Abstract : Ketonuria accompanying hypoglycaemia is conventionally thought to exclude fat oxidation defects. We describe a 2 year old girl with hypoglycaemic encephalopathy in whom a diagnosis of very long chain acyl CoA dehydrogenase deficiency was suggested on the basis of acylcarnitine analysis despite massive ketonuria.